Impactos de la minería aurifera aluvial, en el deterioro de la microcuenca del río Huepetuhe, Madre de Dios - Gonzalez Cruz, Nelly Del Carmen (2014)
The present thesis, "Impact of the alluvial gold mining in the deterioration of the watershed of the Huepetuhe river, Madre de Dios - Peru", presents an analysis of the environmental problematic ofthe auriferous mining industry in Madre de Dios which is of special interest to be totally degraded. The mining auriferous alluvial activity, in a period of 33 years 1980 - 2013, has converted approximately 4,494.41 hectares of natural forest to naked soil. The objective of the study is to determine the environmental irnpacts caused by the alluvial gold mining activity in the surface water and forest coverage of the study area. So that it helps to understand the environmental problematic. In such a way that the local population is conscious that his own actions have contributed to the deterioration of the ecosystem of the micro basin Huepetuhe. The environmental irnpacts identification are made on the basis ofthe literature review, checklists, interviews and field work. While the study of the quality of surface water and deforestation is based on analysis of water samples, satellite images, interviews and field work. In the mining impacts phase; which in turn generate other on the physical environment, biological and social are: deforestation, soil removal, alteration of the morphology and channels, alteration of the surface flow, oil pollution, noise and others. Between them, deforestation is the most indirect impacts generated the most serious deterioration of the ecosystem of the study area. During the mineral benefit phase, mercury is emitted to the atmosphere by evaporation during its use and burning; as well as for discharges and accidental spills to the ground and water. From the results, there is demonstrated that the auriferous alluvial mining industry, it is ~;